Incarceration of a colonoscope in an inguinal hernia: A report of two cases. Issue 1 (10th May 2022) - Abe, Yuno; Ohya, Yuki; Nakahara, Osamu; Chiyonaga, Suguru; Maeda, Yuto; Ichikawa, Ryo; Imamura, Miyuki; Yamabe, Satoshi; Morinaga, Takeshi; Tsuji, Akira; Hayashida, Shintaro; Iizaka, Masayoshi; et al.
Abstract: We report two cases of the rare complication of a colonoscope incarcerated in an inguinal hernia. The first patient was a 73‐year‐old man in whom a colonoscope was incarcerated in a left inguinal hernia on attempted withdrawal. The incarcerated colonoscope was successfully reduced manually under fluoroscopic guidance. The hernia was subsequently repaired using an extraperitoneal approach followed by a successful colonoscopy. The second patient was a 74‐year‐old man in whom the colonoscope became incarcerated in a left inguinal hernia on insertion. Similar to the first case, the colonoscope was manually reduced under fluoroscopy and the entire colonoscopy was then uneventfully performed. An advanced sigmoid cancer was identified and treated with sigmoidectomy. The hernia resolved after this operation. When a colonoscope becomes incarcerated in an inguinal hernia, the manual reduction should be attempted. Subsequent colonoscopy can be safely performed under certain circumstances.